2021
DOI: 10.1021/jasms.0c00471
|View full text |Cite
|
Sign up to set email alerts
|

Flash Oxidation (FOX) System: A Novel Laser-Free Fast Photochemical Oxidation Protein Footprinting Platform

Abstract: Hydroxyl radical protein footprinting (HRPF) is a powerful and flexible technique for probing changes in protein topography. With the development of the fast photochemical oxidation of proteins (FPOP), it became possible for researchers to perform HRPF in their laboratory on a very short time scale. While FPOP has grown significantly in popularity since its inception, adoption remains limited due to technical and safety issues involved in the operation of a hazardous Class IV UV laser and irreproducibility oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…Streamlining the FPOP workflow would further facilitate the adoption of these methods to a broad audience. Recently, a flash oxidation (FOX) system was developed for performing HRPF using a high-pressure flash lamp for photolysis of H 2 O 2 . This system eliminates the use of the laser, whose safety issues may limit the adoption of laser-based HRPF by some laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streamlining the FPOP workflow would further facilitate the adoption of these methods to a broad audience. Recently, a flash oxidation (FOX) system was developed for performing HRPF using a high-pressure flash lamp for photolysis of H 2 O 2 . This system eliminates the use of the laser, whose safety issues may limit the adoption of laser-based HRPF by some laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of Sequest and Bolt for IC-FPOP showed that Bolt identified a 1.5-fold greater number of modified peptides in 64 h of computational time compared to 203 h for Sequest, thus increasing throughput and the amount of structural information. Finally, the recently developed FoxWare protein footprinting software has been successful in quantification of HRPF modifications . Even with these advancements, data analysis is still the most time-consuming and complex part of HRPF studies.…”
Section: Discussionmentioning
confidence: 99%
“…FPOP experiments often require laser irradiation within flow injection manifolds to control the oxidation reactions used for protein labeling . More recent versions of FPOP operate without the need of lasers, offering the potential to measure protein stabilities directly through the direct observation of protein oxidation rates and are moving toward in vivo proteome-wide assessments of protein stability values. Future advancements in FPOP will likely continue along this trajectory, further enabling the measurement of protein and protein complex stabilities on a proteome scale. , …”
Section: Survey Of Ms-based Protein Stability Measurement Techniquesmentioning
confidence: 99%
“…10 Many methods of generating hydroxyl radicals have been developed over recent decades and are currently routinely employed, including radiolysis of water by X-rays, gamma rays, electron beams, electric discharge or a plasma source, decomposition of hydrogen peroxide using transition metal based Fenton chemistry and photolysis of hydrogen peroxide using lasers or a high-pressure flash oxidation lamp. [11][12][13][14][15] Independent of the method of production, •OH are highly reactive species and have van der Waals surface area and solvent properties similar to those of water molecules. 14 •OH are polar moieties, react irreversibly with side chains on the order of microseconds and can routinely modify 12 out of the 20 amino acids in HRPF experiments.…”
Section: Introductionmentioning
confidence: 99%